2003
DOI: 10.1007/bf03403564
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Misclassification Rate of Self-reported Visual Disability

Abstract: Purpose: To estimate the misclassification rate of self-reported visual disabilities in a hospital-based population with known visual impairment. Methods: Subjects (N=570) were recruited among patients aged 50 years and more and classified to three categories of visual impairment level. The questionnaire was administered to consenting patients through a telephone interview. Data collected from questionnaires and medical records were compared regarding severity of visual impairment. Sensitivity and specificity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However self reports of visual impairment is an acceptable and useful way of determining visual acuity in epidemiological surveys and has been found to correlate well with objective measures of visual acuity in previous studies. 20,21,22 Analysis of test-retest assessment of self reports of the respondents showed that they were reliably made. Quality of life was measured by self-report, using a generic rather than a vision-specific tool.…”
Section: Discussionmentioning
confidence: 99%
“…However self reports of visual impairment is an acceptable and useful way of determining visual acuity in epidemiological surveys and has been found to correlate well with objective measures of visual acuity in previous studies. 20,21,22 Analysis of test-retest assessment of self reports of the respondents showed that they were reliably made. Quality of life was measured by self-report, using a generic rather than a vision-specific tool.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 570 persons aged 50 years and older, questions related to visual acuity were found to have a sensitivity of approximately 82% and a specificity ranging from 87% to 89%. 51 However, visual acuity, contrast and glare sensitivity, stereoacuity, and visual fields are significant independent risk factors for self-reported visual disability in the elderly, and visual acuity alone is not the only dimension of subjective visual disability. 52 Agreement between self-reported hearing loss and pure-tone airconduction audiometry has a sensitivity ranging from 76% to 93% and a specificity ranging from 56% to 82%.…”
Section: Commentmentioning
confidence: 99%
“…For example, in one study, the specificity and sensitivity of self-reported VI with clinical visual acuity measures as the ‘gold standard’ range from 82%–89%. 36 In another study, the concordance of distance acuity results with the question “Are you able to recognize a face from a distance of four meters” was reported to be 79%. 37 However, the use of visual acuity as the ‘gold-standard’ or the only dimension of VI to evaluate self-reported VI is subject to its own limitations given that other components of the visual system can affect visual functioning.…”
Section: Discussionmentioning
confidence: 95%